Minimal Damage to the Supinator Muscle After the Double-Incision Technique for Distal Biceps Tendon Repair. Issue 12 (10th December 2020) - Blonna, Davide; Olivero, Alberto; Galletta, Claudia; Greco, Valentina; Castoldi, Filippo; Fracassi, Matteo; Davico, Marco; Rossi, Roberto
Background: The effect of the double-incision technique on the supinator muscle is unclear. Purpose: The aim of this study was to quantify fatty atrophy of the supinator muscle and map the area of muscle damage. Study Design: Case series; Level of evidence, 4. Methods: A total of 19 male patients (median age, 43 years) who underwent distal biceps tendon repair were included in the analysis. Patients with a minimum of 12 months of follow-up were included. The following variables were analyzed: range of motion; shortened version of Disabilities of the Arm, Shoulder and Hand (QuickDASH) score; Summary Outcome Determination (SOD) score; and isokinetic peak force and endurance in supination. Quantitative analysis and mapping of fatty infiltration of the supinator muscle were based on the calculation of proton density fat fraction on magnetic resonance imaging scans of both elbows using the IDEAL (Iterative Decomposition of Echoes of Asymmetrical Length) sequence. Results: At an average follow-up of 24 months (range, 12-64 months), the median SOD score was 9.0 (95% CI, 7.8-9.4), and the mean QuickDASH score was 6.7 (95% CI, 0.0-14.1). A difference of 17% in peak torque was measured between repaired and nonrepaired elbows (repaired elbow: 9.7 N·m; nonrepaired elbow: 11.7 N·m; P = .11). Endurance was better in the repaired elbow than the nonrepaired elbow (8.4% vs 14.9% work fatigue, respectively; P = .02). The average fat fraction of the supinator muscle was 19% (95% CI, 16%-21%) in repaired elbows and 14% (95% CI, 13%-16%) in contralateral elbows ( P = .04). The increase in fat fraction was located in a limited area between the radius and ulna at the level of the bicipital tuberosity. Conclusion: The assessment of the supinator muscle showed a limited increase in fat fraction between the radius and ulna at the level of the bicipital tuberosity. No significant effect on supination strength was highlighted.